Development of Midwifery Documentation System In Web-Based Pregnancy Care - Dewi Susilawati; Nilakesuma, Nur Fadjri; Syahid, Armein (Window of Health : Jurnal Kesehatan, 2025)
Documentation of pregnancy care is very important to monitor the health of the mother and the fetus she is carrying; often, this documentation is still done manually and sometimes irregularly. There is a need for a midwifery documentation system that can assist students in recording data regularly and accurately. SOAP of Midwifery Documentation (MD-SOAP) is a web-based documentation system designed based on the needs in documenting pregnancy care, starting from a thorough assessment of the patient's basic data, diagnosis, care planning, implementation, and evaluation based on the Varney mindset with SOAP documentation that is written in narrative. The purpose of this study was to identify the need for midwifery documentation in pregnancy care and design a prototype of SOAP of Midwifery Documentation (MD-SOAP). This research method is Research and Development (R&D) to design a prototype of SOAP of Midwifery Documentation (MD-SOAP). The sample of this study was part of the Midwifery Study Program students of STIKes MERCUBAKTIJAYA Padang, as many as 88 students. Data collection techniques by filling out questionnaires. Analysis of this research is descriptive, quantitative, and qualitative. The results of this study are the need for web-based midwifery documentation, obtained 100% of students stated the need for web-based documentation. So far, they have used documentation by handwriting methods, 83% understand the use of computers, and 72.4% understand the use of the web. The features available in MD-SOAP cover all aspects needed in pregnancy care. MD-SOAP has also been validated by media experts and midwifery experts specializing in pregnancy care, all of whom stated that this web is suitable for use. The results of this study conclude that the MD-SOAP web is suitable for use by students in documenting pregnant women.